Preliminary qualitative findings on technology adoption of Malaysian SMEs - Abdullah, Nor Hazana (2012)
Technology has been recognized as one of strategic resources for sustaining competitiveness among firms regardless of their sizes. Challenges in globalizations and strategic alliances are some of the issues underpinning technology adoption among SMEs. However, existing models on technology adoption have not provided sufficient insights on factors that could influence the successful adoption of technology among SMEs in Malaysia. In particular, uniqueness of SMEs characteristics, especially in terms of pervasive influence of SMEs’ owner-managers, has not been considered. Therefore,this study aims to identify significant factors that could have pervasive influence on technology adoption among SMEs in Malaysia by integrating internal and external factors together with the SME unique characteristics. A preliminary study was conducted to propose the SME technology adoption model to validate the influence of external factors, internal factors and SMEs’ owner-manager characteristics. This study employed multiple case study strategy as its research design and interviews as primary data collection method. Collected data were analyzed using thematic analyses to identify recurring factors across cases.The findings showed that notwithstanding of the technologies adopted by the firms, internal factors and SME’s ownermanagers characteristics have significant influence on technology adoption among SMEs.